ОКРЕМІ АСПЕКТИ АДМІНІСТРАТИВНО-ПРАВОВОГО РЕГУЛЮВАННЯ СФЕРИ ТУРИЗМУ - Чорненький, Василь Володимирович (SUPREMANCE OF LAW, 2018)
The article is devoted to the study of the state of the administrative and legal regulation of the sphere of tourism, which in the present situation plays a significant role for increasing the level of mobility and employment of the population of Ukraine, contributes to the stable growth of its economy, rational use of objects of cultural and natural heritage.